Polyphosphate as a Target for Interference With Inflammation and Thrombosis - Mailer, Reiner K. W.; Hänel, Lorena; Allende, Mikel; Renné, Thomas (Frontiers in Medicine, 2019)
The factor XII (FXII)-driven plasma contact system initiates thrombosis by the intrinsic coagulation pathway and vascular hyperpermeability by bradykinin production. Conversion of FXII zymogen into the activated serine protease FXIIa is initiated through binding to the inorganic polymer, polyphosphate (polyP). PolyP is exposed on surfaces of activated platelets and mast cells and has been recognized as a therapeutic target to interfere with FXIIa-mediated cascades in blood coagulation and vascular hyperpermeability. PolyP metabolism has mainly been studied in bacteria and yeast, but its roles in eukaryotic cells and mammalian systems have remained enigmatic. PolyP content and chain length depend on the specific cell type and energy status, which may affect cellular functions. In this review, we will present an overview of polyP functions, focusing on intra- and extracellular roles of the polymer and discuss open questions that emerge from the current knowledge on polyP metabolism.